Rapid detection of porins by matrix-assisted laser desorption/ionization-time of flight mass spectrometry - Hu, Yan-Yan; Cai, Jia-Chang; Zhou, Hong-Wei; Zhang, Rong; Chen, Gong-Xiang (Frontiers in Microbiology, 2015)
The rapid and cost-efficient determination of carbapenem resistance is an important prerequisite for the choice of an adequate antibiotic therapy. A MALDI-TOF MS-based assay was set up to detect porins in the current study. A loss of the components of porin alone such as OmpK35/OmpK36 or together with the production of carbapenemases will augment the carbapenem resistance. Ten strains of E. coli and eight strains of K. pneumoniae were conducted for both SDS-PAGE and MALDI-TOF MS analysis. MALDI-TOF/TOF MS analysis was then performed to verify the corrospondence of proteins between SDS-PAGE and MALDI-TOF MS. The results indicated that the mass spectrum of ca. 35,000-m/z, 37,000-m/z and 38,000-m/z peaks of E. coli ATCC 25922 corresponded to OmpA, OmpC and OmpF with molecular weight of approximately ca. 38 kDa, 40 kDa and 41 kDa in SDS-PAGE gel, respectively. The band of OmpC and OmpF porins were unable to be distinguished by SDS-PAGE, whereas it was easy to be differentiated by MALDI-TOF MS. As for K. pneumoniae isolates, the mass spectrum of ca. 36,000-m/z and 38,600-m/z peaks was observed corresponding to OmpA and OmpK36 with molecular weight of approximately ca. 40 kDa and 42 kDa in SDS-PAGE gel, respectively. Porin OmpK35 was not observed in the current SDS-PAGE, while a 37,000-m/z peak was found in K. pneumoniae ATCC 13883 and carbapenem-susceptible strains by MALDI-TOF MS which was presumed to be the characteristic peak of the OmpK35 porin. Compared with SDS-PAGE, MALDI-TOF MS is able to rapidly identify the porin-deficient strains within half an hour with better sensitivity, less cost, and is easier to operate and has less interference.